Performance study of modified designs of a ranque-hilsch vortex tube using geometry parameters and helical tapes in the hot tube / Nurhasanah Ismail - Ismail, Nurhasanah (2018)
This thesis contains a study about the effect of basic parameters (inlet pressure, orifice diameter, conical valve angle and nozzle height) and the addition of helical tapes in a hot tube on the performance of the Ranque-Hilsch Vortex Tube model A20400. There are two types of investigation that have been conducted in this study: (1) experimental and (2) numerical investigation. In the experimental investigation, the inlet pressure, orifice diameter, nozzle's height and conical valve angle were tested and their effects on the performance of the Ranque-Hilsch vortex tube were analyzed. From the experiment, it was observed that the swirl generator gave the most significant effect (isentropic efficiency 21%) on the performance of the Ranque-Hilsch Vortex Tube compared to other parameters. The phenomenon of vortex flow in the tube gave significant impact to the performance of Vortex Tube in terms of temperature separation. Then the research continued with improving the performance using numerical investigation by adding helical tapes in the hot tube of the Ranque-Hilsch Vortex Tube. Three revolutions numbers of helical tapes were used: 1.5 revolutions, 2.5 revolutions and 3 revolutions. The results show that by adding the helical tape on the tube wall, it helps to expand the cold temperature region that is located at the center of the tube and it reduces the temperature at the cold end of the Ranque-Hilsch vortex tube. In this study, the 1.5 revolutions helical tape resulted in the most expanded cold region and resulted in the lowest temperature compared to the others.